Playing the algorithm: Mobile gamers’ everyday (in)visibility strategies - Willson, Michele; Kinder-Kurlanda, Katharina (AoIR Selected Papers of Internet Research, 2016)
Internet users are increasingly aware that they generate data traces and that they are acting in spaces in which algorithms operate. Games on mobile phones or tablets, similar to many other mobile apps, enable the collection and analysis of user data. These analyses are performed by simple or complex algorithms.In this paper, we examine the everyday practices of casual gamers in their interaction with mobile games as algorithmic spaces. We are particularly interested in how casual gamer awareness of these practices alongside broader privacy concerns are navigated. Through the use of qualitative interviews and a questionnaire, we investigate the practices of casual mobile gamers around their management of visibility and invisibility. We consider these practices as ways of managing privacy requirements within algorithmic public spheres.Australian and German mobile game play will be explored in order to identify similarities and differences in practices of situated algorithmic management in the everyday. Germany has been the locus of considerable concern about online privacy, and part of the impetus behind the right to be forgotten data protection legislation. It therefore should pose an interesting site of comparison with Australia, where similar concerns have been evinced but are less evident within the broader public discourse and in legislative approaches.